Metode Dakwah Islam, Katolik dan Penghayat di Kelurahan Cigugur Kabupaten Kuningan - Alamsyah, Fahmi; Suherdiana, Dadan; Bahrudin, Bahrudin (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to find out the methods of proselytizing Islam, Catholicism, and Penghayat in Cigugur Village, Kuningan Regency. The theories used in this research include SWOT analysis theory and comparative da'wah theory. The research method used is a qualitative method with researchers who trace the da'wah method of the object under study. The results showed that each teaching in Cigugur has its own dynamics. The method of spreading Catholicism proves to be superior to other religions, although the number of adherents is still inferior to Islam. On the other hand, penghayat does not have a specific goal to invite people into its beliefs. The adherents of penghayat continue to decrease every year and tend to turn to religions that are â€œrecognizedâ€ by the state.